Oxytetracycline residues in Sheep meat in Khartoum State, Sudan - Yousif Hussein, Ahmed El Rayah; Elmansoury, Yousif Hussein; Hussien, Mohammed Osman; Taha, Mohammed Idress; Mahgoub, Hoyam Awad; El Hussein, Abdelrahim Mohamed (Journal of Advanced Veterinary and Animal Research, 2015)
In the last two decades, the chemical and biological contaminants in livestock and livestock products worldwide have been considered as one of the causes that threatens life of both man and animals. In Sudan very little work has been done in this field. This study was carried out to detect Oxytetracycline (OTC) residues in sheep liver and muscle samples in Khartoum State, Sudan. A total of 150 samples comprising of liver (n=75) and muscle (n=75) of sheep were collected from three different localities in Khartoum State during the period from March to September 2013. The OTC residues were detected using high performance liquid chromatography (HPLC) and one plate test (OPT). The results of HPLC showed that the level of OTC residues in liver samples above maximum residue limit (MRL) was 4% (n=3/75) and under MRL was 96%. Regard to muscle samples, the level of OTC residues above MRL was 60.3% (n=35/58), whereas, under MRL was 39.7%. Using OPT, 14.7% (n=11/75) and 6.7% (n=5/75) of liver and muscle samples showed inhibition zone, respectively. It is concluded that OTC residues are detected in sheep liver and muscle sample with different levels in Khartoum state. Further investigation on level of OTC residues in other farm animals and other organs throughout the country is recommended. http://dx.doi.org/10.5455/javar.2015.b101